Инновационная технология получения хромированных диффузионных покрытий с использованием композиционных насыщающих сред - Середа, Борис Петрович; Кругляк, Ирина Васильевна; Кругляк, Дмитрий Олегович (НТУ "ХПІ", 2018)
Рассмотрена инновационная технология формирования хромированных покрытий с использование 6 м композиционных насыщающих сред на конструкционных материалах и сплавах. исследованы закономерности и механизмы формирования диффузионных покрытий. установлена зависимость толщины покрытий от технологических параметров процесса. С использованием методов математического моделирования разработаны оптимальные составы композиционных насыщающихся сред для нанесения комплексных покрытий. Изучено влияние составов композиционных насыщающихся сред на свойства полученных покрытий. С целью анализа процесса формирования хромированных диффузионных покрытий с использованием композиционных насыщающих сред выполнен расчет равновесного состояния продуктов реакций в многокомпонентных композиционных системах.

An innovative technology for the formation of chrome-plated coatings with the use of 6m composite saturating media on structural materials and alloys is considered. The laws and mechanisms of the formation of diffusion coatings are investigated. The dependence of the thickness of the coatings on the technological parameters of the process was established. Using the methods of mathematical modeling, optimal compositions of composite saturating media have been developed for the application of complex coatings. In this paper, the technology of chemical-heat treatment of steels under non-stationary temperature conditions combined with chemical gas transport reactions is considered. The effect of the composition of saturating composite media on the properties of the coatings obtained was studied. The process of chromium plating, like boronation, is an effective method of increasing the reliability and durability of machine parts, tools and tooling by creating chromium-plated layers on the surface of the workpiece with a unique set of physicochemical properties. For the purpose of analyzing the process of the formation of chromated diffusion coatings using composite saturating media, the equilibrium state of the reaction products in multicomponent composite systems has been calculated. Chrome coatings on steels and alloys can significantly improve the corrosion resistance, heat resistance, hardness and wear resistance, and often get the required combinations.
Innovative technology of obtaining chromated diffusion coatings using composite powder medium
Keywords: химические транспортные реакции; математическое моделирование; коррозионная стойкость; диффузия; плотность; пористость; микротвердость; composite saturating media; coating; mathematical modeling; corrosion resistance; diffusion; density; porosity; microhardness